La información sobre el origen biológico como derecho fundamental de la persona - Cárdenas Krenz, Arturo Ronald (2013)
This paper examines whether people conceived through assisted reproductive techniques are entitled to know their biological origin, in the context of the fundamental rights of every human being, even though a large majority of countries currently denies that right.